Forecasting and Measuring The Impact on Non-Tax Revenue of Its Principal Determinants in Nepal - Arjun Kumar Dahal (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This study aims to examine the impact on non-tax revenue of its principal determinants like charges, fines, fees, forfeiture, dividend, principal and interest payment, income received from sales, Royalty, and sales from fixed assets. It also explores the ex-post forecasting of non-tax revenue. It is based on the secondary data taken from various economic surveys of Nepal covering from 1980 to 2019. Descriptive and exploratory research designs are used to examine the impact and forecast the dependent variable. Some statistical and econometric tools like descriptive statistics, unit root testing, ordinary least square, serial correlation, heteroscedasticity test, and dynamic ex-post forecasting approaches. There is a positive impact on non-tax revenue of its principal determinants. The income received from principal and interest payment is found more consistent, whereas the non-tax revenue from sales government goods and services is found more inconsistent than other variables. The value of root means squared error is encountered very small (i.e., 0.7865). So, the gap between actual and forecasted nom-tax revenue is tiny. The results, design, and techniques of this study are not affected by the results and findings of other researchers